Effect of Financial Performance on Stock-Prices in Food and Beverages Firm - Alam, Nur; Aida, Nur; Mukhtar, Afiah (Golden Ratio of Finance Management, 2021)
This study examines the effect of financial ratios on Food and Beverage stock prices (F&B). The study uses a sample of Food and Beverage firms listed on the IDX period 2017-2019. By the 31 companies as the population, we decided the sample just 14 F&B companies; the study's total sample was 42 financial statements and annual reports with the purposive sampling method. Hypothesis testing was used in this study using multiple linear regression analysis. This study indicates that Return on Equity (ROE) has a significant positive effect on stock prices. In contrast, Return on Assets (ROA), Net Profit Margin (NPM), Current Ratio (CR), Debt to Equity Ratio (DER), and Debt to Assets Ratio (DAR) partially has no significant effect on stock prices. Therefore, first, the company should pay attention to the level of the company's liability. The ratios related to the comparison with debt tend to be at a safe point from financial distress to increase the company's share price, especially in the food and beverage sub-sector. Secondly, for investors to invest in companies, especially the food and beverage sector, they need to pay attention to Return on Equity (ROE) because it significantly affects its stock price with this ratio.